FENOMENA CHILDFREE DALAM PERSPEKTIF MAQASHID AL-SYARIAH - Utari, Agni; Sabaruddin; Darwis, Rustan (MADDIKA : Journal of Islamic Family Law, 2024)
The childfree phenomenon has been developing and has become an interesting topic of discussion in Indonesian society, triggering diverse pro and contra reactions. The increased visibility of this issue is partly influenced by the statement of influencer Gita Savitri Devi, which subsequently fostered public discourse concerning the childfree life choice. Given the significance of this phenomenon and the polemic it has generated, this research aims to analyze the childfree phenomenon in Indonesia and examine how the perspective of Maqashid al-Syari’ah addresses this life choice. This study employs library research, utilizing Normative Theological and Sociological Approaches. The research findings indicate that the childfree life choice is underpinned by various considerations and reasons from the individuals or couples who make this decision. From the perspective of Maqashid al-Syari’ah, gaining an in-depth understanding of these reasons is crucial for the analysis. Consequently, if the reason for choosing childfree aligns with the principle of maslahah dharuriyyat within the framework of Maqashid al-Syari’ah, the decision could potentially be deemed permissible, and vice versa